Vertical handover decision algorithm in heterogeneous wireless networks. (2017) - Benaatou, Wafa; Latif, Adnane; Pla, Vicent
With the recent progress in the area of cellular communication the issue of inter cells handover without dropping an ongoing connection with the base station has arisen. In this paper, the focus is on the performance of vertical handover. Various proposed interconnection architectures for vertical handover in heterogeneous networks were studied. Two different algorithms to make the decision on when and to which network perform a handover were considered. In the first of them the decision is based on the received signal strength (RSS). In the second one a fuzzy logic system that uses RSS, bandwidth, battery power and packet loss as the input parameters is proposed. The simulation results show that the algorithm based on fuzzy logic leads to a reduction of the number of handovers and a minimisation of the power consumption as compared to the first algorithm used here and the existing algorithms.